Stress among nurses working in critical care areas at a tertiary care teaching hospital, Nepal - Mehta, R K; Singh, I K (Journal of Chitwan Medical College, 2015)
Stress is a part of our life. Stress can also create positive and negative influence in our daily lives. As a positive influence stress is a motivating force towards progress and it can create new awareness and exciting new perspective. As a negative influence it creates feeling of distress, rejection, depression, which leads to variety of physical and psychological problems. The aim of the study was to assess stress among nurses working in critical care areas at BPKIHS. A Descriptive explorative design was used to conduct the study in critical care areas of BPKIHS Dharan. Fifty staff nurses working in critical care areas with at least one year of critical care experience were included in this study. Random sampling technique was used to select the sample from random number table. Self administered structured questionnaire and Modified Expanded Nursing Stress Scale were used for the collection of data. Study findings revealed that majority of the respondents 56% had moderate stress followed by mild stress 34%, sever stress 6%, where as very less number of respondents 4% had no stress in their job setting. This study finding also indicate that Nepalese nurses rated factors such as lack of opportunity to discuss problems with peers 36% and inadequate emotional preparation 30%, being sexually harassed 24%, experiencing discrimination because of race or ethnicity 20%, and experiencing discrimination on the basis of gender 10% as low on the stress scale. Stress factors rated “Moderately and very much stressful” were shortage of staff to adequately cover the unit 82%, being blamed for anything that goes wrong 70%, not enough equipment supplies/not functioning well 62%, physician not being present in a medical emergency 62%, patients’ family making unreasonable demands 62%, lack of support from nursing administration 52%, having to work through breaks 54%, not enough time to complete all nursing tasks 46%. This study provides valuable insight into the actual and perceived stressful experiences of critical care nurses, thus contributing to the ongoing effort to reduce burnout in this population. DOI: http://dx.doi.org/10.3126/jcmc.v4i4.11972